Human Resource Optimization: Best Practices in Talent Management and Organizational Performance - Wiwit Damayanti (PT. Publikasiku Academic Solution, 2023)
Human resources are one of the important assets for a company or organization. Maintaining high-value human resources is not something that is easy. Many workers in the millennial generation leave or leave the company without any clear reason, this is what many resource management are afraid of. human power. Because losing a worker is a normal thing that happens and burdens the company, such as lost productivity and damaged morale are one of the reasons behind the high price of losing a worker, therefore an optimal strategy is needed so that employees are comfortable and loyal to the organization or company. The aim of this research is to find out what efforts to optimize human resources are like. This research uses descriptive qualitative research methods and library research which is useful for expanding the discussion. The results of this research are that optimization efforts carried out by implementing talent management strategies by providing training, mentoring and education for employees can have a significant impact on performance for companies or government organizations.